Prolonged Cannabidiol Treatment Lacks on Detrimental Effects on Memory, Motor Performance and Anxiety in C57BL/6J Mice - Schleicher, Eva M.; Ott, Frederik W.; Müller, Melanie; Silcher, Barbara; Sichler, Marius E.; Löw, Maximilian J.; Wagner, Jannek M.; Bouter, Yvonne (Frontiers in Behavioral Neuroscience, 2019)
The Cannabis plant contains more than 100 currently known phytocannabinoids. Regarding the rising consume of the non-psychotropic phytocannabinoid Cannabidiol (CBD) in people’s everyday life (e.g. beauty products, food and beverages), the importance of studies on the influence of CBD on healthy humans and rodents is evident. Therefore, the behavioral profile of CBD was investigated with a battery of behavioral tests, including motor, anxiety, and memory tests after prolonged CBD treatment. Adult C57Bl/6J wildtype mice were daily intraperitoneal injected with 20mg/kg CBD for six weeks starting at two different point of ages (3 months and 5 months) to compare the influence of prolonged CBD treatment with a washout period (former group) to the effects of long term CBD treatment (current group). Our results show that CBD treatment does not influence motor performance on an accelerating Rotarod test, while it also results in a lower locomotor activity in the Open Field. No influence of CBD on spatial learning and long term memory in the Morris Water Maze was observed. Memory in the Novel Object Recognition test was unaffected by CBD treatment. Two different anxiety tests revealed that CBD does not affect anxiety behavior in the Dark-Light Box and Open Field test. Although, anxiety is altered by current CBD treatment in the Elevated Plus Maze. Moreover, CBD treated C57Bl/6J mice showed an unaltered acoustic startle response compared to vehicle treated mice. However, current CBD treatment impairs Prepulse Inhibition, a test to analyze sensorimotor gating. Furthermore, prolonged CBD treatment did not affect the hippocampal neuron number. Our results demonstrate that prolonged CBD treatment has no negative effect on the behavior of adult C57Bl/6J mice.